Recovery of Rare Earth Elements from Low-Grade Feedstock Leachates Using Engineered Bacteria - Park, Dan M; Brewer, Aaron; Reed, David W; Lammers, Laura N; Jiao, Yongqin (Environmental science & technology, 2017)
The use of biomass for adsorption of rare earth elements (REEs) has been the subject of many recent investigations. However, REE adsorption by bioengineered systems has been scarcely documented, and rarely tested with complex natural feedstocks. Herein, we engineered E. coli cells for enhanced cell surface-mediated extraction of REEs by functionalizing the OmpA protein with 16 copies of a lanthanide binding tag (LBT). Through biosorption experiments conducted with leachates from metal-mine tailings and rare earth deposits, we show that functionalization of the cell surface with LBT yielded several notable advantages over the nonengineered control. First, the efficiency of REE adsorption from all leachates was enhanced as indicated by a 2–10-fold increase in distribution coefficients for individual REEs. Second, the relative affinity of the cell surface for REEs was increased over all non-REEs except Cu. Third, LBT-display systematically enhanced the affinity of the cell surface for REEs as a function of decreasing atomic radius, providing a means to separate high value heavy REEs from more common light REEs. Together, our results demonstrate that REE biosorption of high efficiency and selectivity from low-grade feedstocks can be achieved by engineering the native bacterial surface.